2018
DOI: 10.1177/1934578x1801300730
|View full text |Cite
|
Sign up to set email alerts
|

Mangifera indica Bark Essential Oil: Chemical Composition and Biological Activities in Comparison with Aqueous and Ethanol Extracts

Abstract: Ethnobotanic surveys have revealed the use of Mangifera indica L. (Anacardiaceae) bark for the treatment of infectious diarrhea. The essential oil of M. indica bark is described for the first time for its chemical composition, radical scavenging activity (DPPH method) and antimicrobial properties. The total phenols content of its water and ethanol bark extracts as well as their radical scavenging and antimicrobial properties were also evaluated. Four commercial plant extracts were also studied for a comparison… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
(14 reference statements)
0
7
0
Order By: Relevance
“…Based on the results, the GLE can thus be applied as a cytotoxic agent in medical treatment. 103 It was also found that the IC 50 values in GLE ranged from 200 mg mL À1 to 250 mg mL À1 against Kasumi-1 leukaemia cells. 101,104 Thus, the cytotoxicity activity of GLE is very signicant to inhibit the growth of these cancer cells.…”
Section: Antibacterial Studymentioning
confidence: 94%
See 1 more Smart Citation
“…Based on the results, the GLE can thus be applied as a cytotoxic agent in medical treatment. 103 It was also found that the IC 50 values in GLE ranged from 200 mg mL À1 to 250 mg mL À1 against Kasumi-1 leukaemia cells. 101,104 Thus, the cytotoxicity activity of GLE is very signicant to inhibit the growth of these cancer cells.…”
Section: Antibacterial Studymentioning
confidence: 94%
“…100 Regarding GLE, the biocompatibility has been demonstrated in many previous studies with the cytotoxicity tests included. [101][102][103] The cell viabilities of CCD-45 SK cells (human healthy skin broblasts) due to the presence of aqueous GLE and ethanolic GLE reached 63% and 93%, respectively. The percentage cell viability of HepG2 (human hepatocellular carcinoma cells) showed more promising results with a value of 50% or even lower.…”
Section: Antibacterial Studymentioning
confidence: 99%
“…The bark has volatile compounds identified in essential oils, presenting terpenoids 26,27 and phenolic compounds such as gallic acid, 3,4-dihydroxybenzoic acid, benzoic acid, methyl gallate, propyl gallate, (+)-catechin, (−)-epicatechin, propyl benzoate, and mangiferin. 28,29 The flowers present gallic acid, ethyl gallate, ethyl digallate, and ellagic acid 30 and volatiles compounds composed of monoterpene hydrocarbons.…”
Section: Distribution Of Phytochemicals In Mangomentioning
confidence: 99%
“…The principal compounds extracted from different mango parts (pulp, peel, seed, leaves, and bark) have been done by SLE, presenting a broad biological activity as can be observed in Table 2. Mango bark presents antimicrobial activity 39,56,57 against Escherichia coli, Salmonella enteritidis, Shigella, Bacillus cereus, Staphylococcus aureus, and Enterococcus faecalis related to its volatile compounds; 26,58 and the leaves present antioxidant, 8,42,59,60 anti-inflammatory, 8,40,61 and antiproliferative activity, 60 due to the presence of phenolic compounds, mainly gallic acid and mangiferin. The peel and pulp extract present antioxidant activity, 23,29,42,43,60,62 and the seed kernel antiproliferative activity.…”
Section: Conventional Extraction Techniquesmentioning
confidence: 99%
“…Although a finite number of studies exist that have explored the effects of essential oils in varied ratios, the majority have considered the use of the isobologram, the most classically applied technique used in studying varying combinations for pharmacodynamic interactions 14 . Although more complicated than the ΣFIC, the isobologram provides an accurate interpretation of the interactions that occur when essential oils are applied in various combinations 7 , 15 . The antimicrobial effect of each essential oil is determined independently and then comparatively assessed against the antimicrobial activity obtained for the ratio.…”
Section: Introductionmentioning
confidence: 99%